Penegakan Hukum terhadap Tindak Pidana Peretasan sebagai Bentuk Kejahatan Mayantara (Cyber Crime) - I Gusti Ayu Suanti Karnadi Singgi; I Gusti Bagus Suryawan; I Nyoman Gede Sugiartha (Warmadewa Press, 2020)
Along with technological developments, there are a lot of facilities available in cyberspace. The development of this technology can also provide opportunities for criminals, especially crimes in cyberspace. Cybercrime is a new form or dimension of a crime that is currently receiving a lot of attention from the international community. One type of cybercrime is hacking. Based on this background, this research was conducted with the aim of describing law enforcement against criminal acts of hacking and the efforts to deal with cybercrime. This research was conducted using normative legal research methods and statutory approaches. The results of this study showed that law enforcement against criminal acts of hacking is regulated in Law Number 19 of 2016 amending Law Number 11 of 2008 concerning Electronic Information and Transactions. The perpetrator will be given criminal sanctions in the form of imprisonment and fines for violations in the field of hacking. In addition, efforts to eradicate cybercrime refers to the Law on Information and Electronic Transactions which is carried out with preventive and repressive measures. Therefore, the criminal act of hacking which is included in the realm of cybercrime has been regulated in Article 30 paragraph (1), (2) and (3) of the ITE Law, while the punishment is regulated in Article 46 paragraph (1), (2), and ( 3) of the ITE Law. In this regard, the government has taken various countermeasures in the form of preventive and repressive measures.